The Study of Bacillus Cereus on a Photonic Crystal Biosensor - Priyadarshini, Rashmi; K Narayanappa, C (International Journal of Engineering and Technology, 2018)
The work involves the study of bacteria named bacillus cereus which is a type of pathogen that causes infections in the blood. This infection of the blood may lead to many more complications that may lead to life threatening. Hence immediate diagnosis becomes an important criteria. B. Cereus is a gram positive and hemolytic bacteria no matter where ever it is extracted from, it requires biomarker to make it recognised and hence the wavelength and refractive index will remain same. The paper includes the study of the presence of B. cereus in the blood with the knowledge of the refractive index of the bacteria with the aid of an photonic crystal nano sized biosensor. The sensor works on the principle of minute changes in the value of the given refractive index value. Namely here the blood samples with the presence of B. cereus and the normal blood sample. The simulation is done where in the design is excited with a Gaussian pulse source with the amplitude differences in wavelength of the two blood samples are observed/. The sensitivity was found to be 5.987Âµm /RIU and the Quality factor is given by 1692.2.Â